2011
DOI: 10.1111/j.1528-1167.2011.03096.x
|View full text |Cite
|
Sign up to set email alerts
|

Swine model for translational research of invasive intracranial monitoring

Abstract: Summary Focal cortical epilepsy is currently most effectively studied in humans. However, improvement in cortical monitoring and investigational device development is limited by lack of an animal model mimicking human acute focal cortical epileptiform activity under epilepsy surgery conditions. Therefore, we assessed the swine model for translational epilepsy research. Swine were used due to their cost effectiveness, convoluted cortex, and comparative anatomy similar to humans. Focal subcortical injection of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 12 publications
3
31
0
Order By: Relevance
“…The swine model was chosen because the large brain volume (pig brain:~160g) is comparable to that of the non-human primate (rhesus monkey brain:~100g) (Hardman et al, 2002; Shon et al, 2010), and with a gyrencephalic cortex, more closely represents human brain anatomy than do the brains of small animal models, such as rodents (Pour-El, 2006; Shon et al, 2010; Van Gompel et al, 2011; Wakeman et al, 2006). We took a novel approach using a high-resolution 3-dimensional pig brain atlas (Saikali et al, 2010), which allowed us to normalize the functional activation map and to apply general linear modeling in each subject group.…”
Section: Introductionmentioning
confidence: 99%
“…The swine model was chosen because the large brain volume (pig brain:~160g) is comparable to that of the non-human primate (rhesus monkey brain:~100g) (Hardman et al, 2002; Shon et al, 2010), and with a gyrencephalic cortex, more closely represents human brain anatomy than do the brains of small animal models, such as rodents (Pour-El, 2006; Shon et al, 2010; Van Gompel et al, 2011; Wakeman et al, 2006). We took a novel approach using a high-resolution 3-dimensional pig brain atlas (Saikali et al, 2010), which allowed us to normalize the functional activation map and to apply general linear modeling in each subject group.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, being similar in size and organization to the brain of the non-human primate [39], [40] the gyrencephalic swine brain, in contrast with the brain of small animals, is more closely representative of the human brain [39], [40], [41], [42]. Specifically, the mean± standard error of the mean (SEM) distance between the anterior commissure and posterior commissure (AC-PC) length for pigs in this study was 12.94±0.30 mm as compared to the 28.3±0.2 mm human AC-PC length that has been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Anesthetic protocols using fentanyl alone or in combination of dexmedetomidine failed to induce adequate sedation as previously described in piglets. 31,40 It is possible that these protocols failed to work in our hands because we induce neuromuscular blockade only after morphine and dexmedetomidine successfully sedated animals to ensure that sedation is adequate during paralysis. Fentanyl is a l-opioid receptor agonist that works well in humans, but we found that morphine, which binds to multiple opioid receptors, worked better as a sedative in piglets, with a dose previously used for anesthesia in elective open heart surgery.…”
Section: Discussionmentioning
confidence: 99%
“…After the surgery to create the injuries, piglets were weaned off isoflurane and a bolus of fentanyl (60-100 lg/kg) followed by a continuous infusion (30-100 lg/kg/h) that was previously reported to induce anesthesia failed to produce adequate sedation alone 40 or in combination with dexmedetomidine (10-30 lg/kg/h). 31 Additional boluses of fentanyl (20 lg/kg) failed to prevent movement, indicating inadequate levels of anesthesia.…”
Section: Creation Of Gaba-independent Seizure-permissive Anesthetic Pmentioning
confidence: 99%